Seminar Kewirausahaan Posko 7 MIT-19 KKN UIN Walisongo: Strategi Branding Digital Untuk UMKM di Desa Bedono - Hava Haniva Ariantara; Meidina Putri; Imanu Massu Barlinti; Malika Latifah Salma; Salsabila Ilmi Rizqika; Baroroh Sofiati; Putri Rahmawati; Alisa Dewi Rahmawati; Tiara Nabilazen; Haris Mayudaee; Meika Puji Andini; Ghilman Kharizi; Yazid Munawwir; Safrida Khoirun Nisa (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The Entrepreneurship Seminar held by Post 7 MiT-19 KKN UIN Walisongo in Bedono Village is part of the community empowerment program, especially in supporting the progress of Micro, Small, and Medium Enterprises (MSMEs). This activity raised the theme "Digital Branding Strategy for MSMEs in Bedono Village" with the goal of increasing the insight and skills of MSME actors in optimizing digital media as a product promotion and marketing tool. This seminar was carried out through the delivery of materials, discussion of case studies, and direct practice of digital content creation. The results of the activity showed an increase in participants' understanding of the importance of building brand identity, the use of social media, and the proper implementation of digital marketing strategies. This activity is expected to be the first step to encourage local MSMEs to be able to compete more widely through digital brand strengthening.